Ca(2+) channel-sarcoplasmic reticulum coupling: a mechanism of arterial myocyte contraction without Ca(2+) influx - Valle-Rodríguez, Alberto del (Oxford University Press, 2003)
Contraction of vascular smooth muscle cells (VSMCs) depends on the rise of cytosolic [Ca(2+)] owing to either Ca(2+) influx through voltage-gated Ca(2+) channels of the plasmalemma or receptor-mediated Ca(2+) release from the sarcoplasmic reticulum (SR). We show that voltage-gated Ca(2+) channels in arterial myocytes mediate fast Ca(2+) release from the SR and contraction without the need of Ca(2+) influx. After sensing membrane depolarization, Ca(2+) channels activate G proteins and the phospholipase C–inositol 1,4,5-trisphosphate (InsP(3)) pathway. Ca(2+) released through InsP(3)-dependent channels of the SR activates ryanodine receptors to amplify the cytosolic Ca(2+) signal. These observations demonstrate a new mechanism of signaling SR Ca(2+)-release channels and reveal an unexpected function of voltage-gated Ca(2+) channels in arterial myocytes. Our findings may have therapeutic implications as the calcium-channel-induced Ca(2+) release from the SR can be suppressed by Ca(2+)- channel antagonists.